Screening, Brief Intervention, and Referral to Treatment (SBIRT) in a retail pharmacy setting: The pharmacist’s role in identifying and addressing risk of substance use disorder. - Shonesy, Brian C. (J Addict Med, 2019)
OBJECTIVE: This study determined the feasibility of interviewing and screening patients presenting to a retail pharmacy using Screening, Brief Intervention, and Referral to Treatment (SBIRT) interview protocols, and to compare SBIRT results to a risk score calculated from Prescription Drug Monitoring Program (PDMP) data. METHODS: Using the NIDA Quick Screen and NIDA Modified-ASSIST (NM-ASSIST) and the Alcohol Use Disorder Identification Test (AUDIT), retail pharmacy customers were screened for substance and alcohol use disorder and tobacco use. PDMP reports were collected on subjects and a PDMP-risk score was calculated based on the numbers of Schedule II-V prescriptions and prescribers over the previous 12 months. RESULTS: A total of 24 patients were included in this study (67% response rate). SBIRT screening revealed that 20.8% were at-risk for substance use disorder, 16.7% for alcohol use disorder, and 37.5% used tobacco. Overall, 33.3% of subjects were at-risk for substance use disorder or alcohol use disorder. Fifty percent of subjects required education and/or brief intervention based on their responses, 37.5% of all subjects were deemed at-risk based on their PDMP-risk score, and 60% of patients who were risk-positive by SBIRT screening were also PDMP-risk positive. CONCLUSIONS: This study demonstrates the feasibility of performing SBIRT-based screenings in a retail pharmacy setting and combining these with PDMP-risk analysis to screen patients for prescription and illicit drug misuse. Findings from this study will inform the design of larger multi-site studies, which should validate these findings and include follow-up analysis to assess the efficacy of intervention on this patient population.